Penerapan Model Pembelajaran Differentiated Instruction untuk Mengoptimalkan Hasil Belajar Siswa di MIS Ar-Rasyid Deli Serdang - Rida Sumanti , Siwi; Wadingah, Siti; Nihayah, Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Each student has different learning characteristics, so uniform teaching approaches are often ineffective in meeting their needs. Differentiated Instruction (DI) comes as a solution by allowing teachers to customise learning strategies based on students’ needs, interests and learning readiness. This study aims to analyse the effectiveness of DI implementation in improving students’ learning outcomes at MIS Ar-Rasyid Deli Serdang, especially in the face of significant academic ability differences. The research method used was Classroom Action Research (CAR) with two cycles involving observation, interviews, questionnaires, and formative tests. The results showed that DI contributed positively to students’ engagement and understanding in learning. Students were more motivated, active in discussions, and showed improvement in learning outcomes. The use of diverse learning strategies, such as project-based learning and group discussion, also plays a role in improving learning effectiveness. However, DI implementation faces challenges in classroom management, time constraints, and teacher training needs. Therefore, support from the school is needed to optimise the implementation of this model. With careful planning, DI can become a more inclusive and adaptive learning strategy, thus improving the overall quality of education